Enhanced neointimal fibroblast, myofibroblast content and altered extracellular matrix composition: Implications in the progression of human peripheral artery restenosis. (August 2016) - Krishnan, Prakash; Purushothaman, K-Raman; Purushothaman, Meerarani; Turnbull, Irene C.; Tarricone, Arthur; Vasquez, Miguel; Jain, Sachin; Baber, Usman; Lascano, Rheoneil A.; Kini, Annapoorna S.; Sharma, Samin K.; Moreno, Pedro R.
Abstract: Background and aims: Neointimal cellular proliferation of fibroblasts and myofibroblasts is documented in coronary artery restenosis, however, their role in peripheral arterial disease (PAD) restenosis remains unclear. Our aim was to investigate the role of fibroblasts, myofibroblasts, and collagens in restenotic PAD. Methods: Nineteen PAD restenotic plaques were compared with 13 de novo plaques. Stellate cells (H&E), fibroblasts (FSP-1), myofibroblasts (α-actin/vimentin/FSP-1), cellular proliferation (Ki-67), and apoptosis (caspase-3 with poly ADP-ribose polymerase) were evaluated by immunofluorescence. Collagens were evaluated by picro-sirius red stain with polarization microscopy. Smooth muscle myosin heavy chain (SMMHC), IL-6 and TGF-β cytokines were analyzed by immunohistochemistry. Results: Restenotic plaques demonstrated increased stellate cells (2.7 ± 0.15 vs. 1.3 ± 0.15) fibroblasts (2282.2 ± 85.9 vs. 906.4 ± 134.5) and myofibroblasts (18.5 ± 1.2 vs. 10.6 ± 1.0) p = 0.0001 for all comparisons. In addition, fibroblast proliferation (18.4% ± 1.2 vs. 10.4% ± 1.1; p = 0.04) and apoptosis (14.6% ± 1.3 vs. 11.2% ± 0.6; p = 0.03) were increased in restenotic plaques. Finally, SMMHC (2.6 ± 0.12 vs. 1.4 ± 0.15; p = 0.0001), type III collagen density (0.33 ± 0.06 vs. 0.17 ± 0.07; p = 0.0001), IL-6 (2.08 ± 1.7 vs. 1.03 ± 2.0; p = 0.01), and TGF-β (1.80 ± 0.27 vs. 1.11 ± 0.18; p = 0.05) were increased in restenotic plaques. Conclusions: Our study suggests proliferation and apoptosis of fibroblast and myofibroblast with associated increase in type III collagen may play a role in restenotic plaque progression. Understanding pathways involved in proliferation and apoptosis in neointimal cells, may contribute to future therapeutic interventions for the prevention of restenosis in PAD. Highlights: Proliferation and apoptosis are basic cellular events in the restenotic plaque. Type III collagen deposition may mediate neointimal expansion. Increase in smooth muscle myosin heavy chain contributes to neointimal expansion. Restenosis was more prevalent in female subjects.